State-of-the-art review of water pipe failure prediction models and applicability to large-diameter mains. Issue 2 (7th February 2017) - Wilson, D.; Filion, Y.; Moore, I.
Abstract: This paper provides an overview of the work performed in the last 13 years to predict the failure of large-diameter trunk water mains. Large-diameter water mains, defined as water mains with a diameter greater than 500 mm, form the main transmission lines in most water distribution systems. The consequences of their failure can be severe and costly. In order for predictive models to be applicable to large-diameter water mains, all models reviewed are capable of analysing individual pipes or pipe segments and calculate either an absolute probability of failure or the hazard of failure relative to other pipes in the system. These models can be divided into two broad categories: physical and statistical models. This review provides a description and a brief critique for each model presented.